Transforming growth factor-β1-induced N-cadherin drives cell-cell communication through connexin43 in osteoblast lineage - Yueyi Yang; Wenjing Liu; JieYa Wei; Yujia Cui; Demao Zhang; Jing Xie (Nature Publishing Group, 2021)
Abstract Gap junction (GJ) has been indicated to have an intimate correlation with adhesion junction. However, the direct interaction between them partially remains elusive. In the current study, we aimed to elucidate the role of N-cadherin, one of the core components in adhesion junction, in mediating connexin 43, one of the functional constituents in gap junction, via transforming growth factor-β1(TGF-β1) induction in osteoblasts. We first elucidated the expressions of N-cadherin induced by TGF-β1 and also confirmed the upregulation of Cx43, and the enhancement of functional gap junctional intercellular communication (GJIC) triggered by TGF-β1 in both primary osteoblasts and MC3T3 cell line. Colocalization analysis and Co-IP experimentation showed that N-cadherin interacts with Cx43 at the site of cell-cell contact. Knockdown of N-cadherin by siRNA interference decreased the Cx43 expression and abolished the promoting effect of TGF-β1 on Cx43. Functional GJICs in living primary osteoblasts and MC3T3 cell line were also reduced. TGF-β1-induced increase in N-cadherin and Cx43 was via Smad3 activation, whereas knockdown of Smad3 signaling by using siRNA decreased the expressions of both N-cadherin and Cx43. Overall, these data indicate the direct interactions between N-cadherin and Cx43, and reveal the intervention of adhesion junction in functional gap junction in living osteoblasts.